1966
DOI: 10.1103/physrev.142.327
|View full text |Cite
|
Sign up to set email alerts
|

Some Properties of Supported SmallαFe2O3Particles Determined with the Mössbauer Effect

Abstract: Mossbauer spectra of Fe 67 in a-Fe 2 0 3 have been measured as a function of particle size and temperature. Bulk a-Fe 2 03 shows a change in the sign of the quadrupole interaction in going through the Morin transition temperature, 263°K. Analyses of the spectra show that the magnetization vector is in the с plane above the transition temperature and parallel to the с axis below it. In contrast, finely divided a-FtzOz particles, sup ported on a high-area silica, do not undergo a Morin transition. The spectra sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
185
2
6

Year Published

1976
1976
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 886 publications
(224 citation statements)
references
References 9 publications
28
185
2
6
Order By: Relevance
“…To confirms that pyrite was decomposed to a-Fe203 at 450, the ME spectrum of a pure natural pyrite sample was measured after heating the sample to 450 O C and the same magnetic pattern was obtained. The ME spectrum of the same sample at liquid nitrogen temperature showed change in the sign of the quadrupole splitting due to Morin transition [15]. This insure that the magnetic pattern which was concluded that Egyptian chalcopyrite ore contains the different phases a, B, and y-CuFeS,, pyrite, sphalerite and sellite.…”
supporting
confidence: 53%
“…To confirms that pyrite was decomposed to a-Fe203 at 450, the ME spectrum of a pure natural pyrite sample was measured after heating the sample to 450 O C and the same magnetic pattern was obtained. The ME spectrum of the same sample at liquid nitrogen temperature showed change in the sign of the quadrupole splitting due to Morin transition [15]. This insure that the magnetic pattern which was concluded that Egyptian chalcopyrite ore contains the different phases a, B, and y-CuFeS,, pyrite, sphalerite and sellite.…”
supporting
confidence: 53%
“…The quadrupole interaction strength and the intrinsic linewidths were fixed to be identical for all spectra in the temperature series and the change of the isomer shift with temperature due to the second order Doppler shift was accounted for using the Debye approximation with a Debye temperature of 500 K. 12,49 Simultaneous fits of this model to the whole temperature series of Mössbauer spectra were performed for both fixed values of 0 between 1ϫ10 Ϫ12 s and 5ϫ10 Ϫ10 s and for 0 as a free parameter. The variation of the quality of the fit, 2 , as a function of ln( 0 ) had a parabola-like minimum. This variation was used for an estimation of the uncertainties on the parameters from the fit.…”
Section: B Analysis Of the Spectra Of The Coated Particlesmentioning
confidence: 94%
“…It is convenient to express the interaction strength in terms of 2 . This is easily carried out in Eqs.…”
Section: Analysis Of the Spectra Of The Dry Samplementioning
confidence: 99%
See 1 more Smart Citation
“…22,24 In ␣-Fe 2 O 3 nanoparticles the spins are confined to lie in the low anisotropy ͑001͒ plane. 25,26 Within this plane, the sublattice magnetization directions can easily rotate while rotation out of the plane requires much more energy. Therefore, superparamagnetic relaxation mainly takes place within the ͑001͒ plane.…”
Section: Introductionmentioning
confidence: 99%